Lessons from special forces operators for elite team sports training: How to make the whole greater than the sum of the parts - Pattyn, N.; Van Cutsem, J.; Van Puyvelde, M.; Cortoos, A.; Roelands, B.; Tibax, V.; Dessy, E.; Huret, M.; Rietjens, G.; Sannen, M.; Vliegen, R.; Ceccaldi, C.; et al. (Frontiers in Sports and Active Living, 2022)
This methodology paper describes the design of a holistic and multidisciplinary human performance program within the Belgian Special Forces Group, the Tier 1 Special Operations unit of the Belgian Defense. Performance management approaches in the military draw heavily on sports science. The key component of the program design described here is its integrative nature, which team sports training might benefit from. The basic rationale behind the program was to bridge several gaps: the gap between physical and mental training; the gap between the curative or preventive medical approach and the performance enhancement approach; and the gap between individual and team training. To achieve this goal, the methodology of Intervention Mapping was applied, and a multidisciplinary team of training and care professionals was constituted with operational stakeholders. This was the first step in the program design. The second step took a year, and consisted of formal and informal consultations, participant observations and task analyses. These two first stages and their conclusions are described in the Method section. The Results section covers the next two stages (three and four) of the process, which aimed at defining the content of the program; and to test a pilot project implementation. The third stage encompassed the choice of the most relevant assessment and intervention tools for the target population, within each area of expertise. This is described extensively, to allow for replication. The fourth and last stage was to "test drive" the real-life integration and implementation of the whole program at the scale of a single team (8 individuals). For obvious confidentiality reasons, the content data will not be reported extensively here. Implications for wider-scale implementation and tie-back to sports team training are presented.